Cognitive performance of military men and women during prolonged load carriage. Issue 1 (7th April 2022) - Armstrong, Nicola C; Smith, S J R; Risius, D; Doyle, D; Wardle, S L; Greeves, J P; House, J R; Tipton, M; Lomax, M
Abstract : Background: This study evaluated cognitive workload in soldiers undertaking a long duration march wearing different loads. Methods: Military participants (n=12 men and n=10 women) performed four 3-hour loaded marches (12.25 km at 4.9 km/hour) wearing either 21 kg, 26 kg, 33 kg or 43 kg. During the march, accuracy and response time were measured using the verbal working memory n-back test (0, 1, 2 and 3) and two bespoke Go/No Go tests (visual/auditory) to assess inhibition of a pre-potent response. Results: The physical demands of the march increased with load and march duration but remained at moderate intensity. N-back test accuracy ranged from 74% to 98% in men and 62% to 98% in women. Reduced accuracy was observed as load and time increased. Accuracy during the visual Go/No Go test also reduced with load, accuracy ranged from 69% to 89% in men and 65% to 90% in women. No differences due to load or time were observed during completion of the auditory Go/No Go task; accuracy ranged from 93% to 97% in men and 77% to 95% in women. A number of participants were unable to complete the march due to discomfort. Reports of discomfort were more frequent in women, which may have contributed to the greater reductions in accuracy observed. Conclusion: These data provide further evidence that cognitive performance of military personnel can be affected during long duration loaded marching. Women reported discomfort from equipment more frequently than men, which may make them more susceptible to declines in cognitive performance. These findings highlight important considerations for equipment procurement.